Evolving OpenMP for evolving architectures : 14th International Workshop on OpenMP, IWOMP 2018, Barcelona, Spain, September 26-28, 2018, Proceedings /: 14th International Workshop on OpenMP, IWOMP 2018, Barcelona, Spain, September 26-28, 2018, Proceedings. (2018) - Unknown
No abstract available